Normative beliefs about aggression as a mediator of narcissistic exploitativeness and cyberbullying - Ang, Rebecca P.; Tan, Kit Aun; Abu Talib, Mansor (Sage Publications, 2011)
The current study examined normative beliefs about aggression as a mediator between narcissistic exploitativeness and cyberbullying using two Asian adolescent samples from Singapore and Malaysia. Narcissistic exploitativeness was significantly and positively associated with cyberbullying and normative beliefs about aggression and normative beliefs about aggression were significantly and positively associated with cyberbullying. Normative beliefs about aggression were a significant partial mediator in both samples; these beliefs about aggression served as one possible mechanism of action by which narcissistic exploitativeness could exert its influence on cyberbullying. Findings extended previous empirical research by showing that such beliefs can be the mechanism of action not only in offline but also in online contexts and across cultures. Cyberbullying prevention and intervention efforts should include modification of norms and beliefs supportive of the legitimacy and acceptability of cyberbullying.